Comparative study of physicochemical composition and microbial community of Khoormog, Chigee, and Airag, traditionally fermented dairy products from Xilin Gol in China. Issue 3 (19th January 2021) - Guo, Liang; Xu, Weiliang; Li, Chundong; Guo, Yuansheng, Yamei; Chagan, Irbis
Abstract: Due to their outstanding nutritional and functional properties, the traditionally fermented dairy products (TFDP) from camel, mare, and cow gained universal praise during their long history of production. In this study, the physicochemical composition and microbial communities of Khoormog, Chigee, and Airag, the TFDP from Xilin Gol in China, were investigated and compared. The physicochemical analysis revealed a higher content of total solid content, protein, and fat in Khoormog (12.5 ± 1.6%; 4.6 ± 0.7%; 4.4 ± 1.3%) compared to Chigee (7.8 ± 1.3%; 2.1 ± 0.2%; 0.8 ± 0.2%) and Airag (8.9 ± 0.7%; 3.7 ± 0.4%; 1.4 ± 0.5%). All three types of TFDP shared 41.2% of bacterial and 25.4% of fungal OTUs, and 95.34% of bacterial and 95.52% of fungal sequence reads. The bacterial and fungal community consisted of four phyla and five genera, and three phyla and seven genera, respectively. Lastly, Lactobacillus predominated in Khoormog, Chigee, and Airag at the genus level, while the dominant fungal genera varied among the samples. In conclusion, the microbial community structures of TFDP from camel, mare, and cow were not significantly different in a definite area (Xilingol region), and Khoormog, Chigee, and Airag bred the common "core microbiota". Abstract : This study is the first to investigate the nutritional properties and microbiota of Khoormog from camel's milk using high throughput sequencing. This study provides the comparative examination of the physicochemical composition and microbial community of Khoormog, Chigee, and Airag.